SPE Middle East Oil &Amp; Gas Show and Conference 2015
DOI: 10.2118/172539-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Influence of Nanoparticles Adsorption and Transport on Wettability Alteration for Oil Wet Berea Sandstone

Abstract: Wettability alteration has been proposed as an important Enhanced Oil Recovery (EOR) mechanism for nanoparticles suspension. For better understanding nanoparticles adsorption behavior inside core and its effect on wettability, a series of wettability measurement experiments for oil wet Berea sandstone were conducted, where the core plugs were treated by different concentration and type of nanoparticles suspensions. Nanoparticles transport experiments also were performed for core plugs with injection of varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…TEM analysis revealed that nanoparticles where attached to the pore walls. Again, the work of Li and Torsaeter [34] was an improved study on wettability alteration and they confirmed earlier reports. Ju et al [26] using a physical model, mathematical model, and a numerical simulator were able to increase recovery by 15.38% when treated with waterwetting wettability control agent (IWWCA) and increasing the oil-wetting wettability control agent (IOWCA) improves recovery (60-80%) in water injection rate.…”
Section: Mechanism Of Wettability Alteration By Nanoparticlessupporting
confidence: 84%
See 2 more Smart Citations
“…TEM analysis revealed that nanoparticles where attached to the pore walls. Again, the work of Li and Torsaeter [34] was an improved study on wettability alteration and they confirmed earlier reports. Ju et al [26] using a physical model, mathematical model, and a numerical simulator were able to increase recovery by 15.38% when treated with waterwetting wettability control agent (IWWCA) and increasing the oil-wetting wettability control agent (IOWCA) improves recovery (60-80%) in water injection rate.…”
Section: Mechanism Of Wettability Alteration By Nanoparticlessupporting
confidence: 84%
“…Adsorption and desorption takes place depending on the attraction and repulsion force between the porous media wall and nanoparticles. During the flow of nanoparticles through porous media, mainly diffusion, convection and hydrodynamics play major role [34]. However, the adsorption of nanoparticles onto rock surface is influenced by born repulsion and controlled by hydrodynamic forces.…”
Section: Nanoparticle Adsorption In Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The small size and high specific surface area of NP offer unique advantages like allowing them to easily pass through pore throats and enhanced interaction in the reservoir even with a small quantity of NP. NPs have displayed the potential to act as surface modifiers that could alter the wettability and reduce the oil/water interfacial tension leading to better mobility of the oil phase [1][2][3][4][5][6][7] and reduce fines migration [8,9]. Recent laboratory studies have indicated that nanofluids, which are colloidal dispersions of NP in a dispersing medium have the potential to increase oil recovery [2,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…When NPs are introduced into porous medium, different processes may take place such as adsorption, desorption, blocking, transportation and aggregation [4]. The adsorption phenomenon could be reversible (desorption) during the transport of NP in the porous medium [20].…”
Section: Introductionmentioning
confidence: 99%